Problems in the Nutrition of Medical University Students (Eurasian Medical Research Periodical, 2023)
It is one of the weakest segments of the population in terms of quality and quantity indicators of Student Nutrition. In this regard, we conducted a study aimed at identifying the peculiarities of the nutrition of students of Samarkand State Medical University